Elections: network building and the web of relationships in local politics in Thailand - nasi, pisit; samnieng, chaipong (King Prajadhipok’s Institute Journal, 2020)
The opportunity for people to enter political space through local administrative organization elections has created massive bargaining power. People gain bargaining power through network building among various interest groups such as family and relatives, national resources based group, and business group. Hence, the local administrative organization becomes an ‘open space’ that people use to create a new form of relationship with the state. Moreover, local elections make local politicians build relationships with people at many levels as well. “Election” then becomes a political tool people use in bargaining with local politicians. Additionally, election gives an opportunity to “new-comers” to enter political space. This indicates that local politics is not monopolized by any one group. Local politics is open for new-comers without limitation within the context of network building in many levels. Local politics is a “bargaining arena”, and importantly is a space for people and self- government.